Electrical and optical studies of dilute nitride and bismide compound semiconductors - Shafi, Muhammad (2011)
A few percent of nitrogen (N) or bimuth (Bi) incorporation in GaAs compound semiconductors have proved to lower significantly its bandgap. This unusual bandgap reduction is of interest for numerous applications such as long wave-length lasers, solar cells etc. However, the addition of these impurity atoms also introduces defect levels in the bandgap of the host materials. These can have severe implications on the material's quality, for example they can decrease the lifetime of the charge carriers and degrade the optical efficiency.